Tecnologia educacional para prevenção da dengue: validação de aparência - Terra, Larice Gonçalves (2017)
Dengue fever is considered one of the major public health problems, along with the zika virus and the chinkungunya fever. The best way to combat these diseases is by eliminating the outbreaks of the Aedes aegypti mosquito. Thus, educational technologies appear as dialogic strategies to encourage the adoption of healthy attitudes. The objective of this study was to validate a booklet for the prevention of dengue among the target public (children, adolescents and adults) in order to make it an Educational Technology. And as specific objectives: to analyze the responses of the target audience regarding the validation of appearance; analyze the comments / suggestions of the target audience, re-evaluate the primer and build the final version. Methodological development research with quantitative-qualitative approach. In the quantitative stage, 217 people participated, through an instrument organized in: objectives; structure; organization and appearance of the booklet. In the qualitative stage, 14 semi-structured interviews were recorded, analyzed and interpreted through the Bardin Content Analysis. The ethical aspects of research with human beings, punctuated in Resolution 466/2012 of the National Health Council, were respected. The items were considered valid, as they reached agreement averages above 0.80. However, changes were made in accordance with the suggestions of the instruments and the interviews, in order to improve it. The item referring to the booklet is appropriate to the adult population did not reach the average of 0.80, however, according to information emerged in the interviews, the validity of this item was ratified. It is concluded that the booklet is an Educational Technology valid to be transferred to children, adolescents and adults.